Environmental Leadership Capacity Building in Higher Education: Experience and Lessons from Asian Program for Incubation of Environmental Leaders - Takashi Mino, Keisuke Hanaki (Springer Nature, 2013)
Environmental Management; Business Ethics; Environmental Science and Engineering; Science Education; Non-Profit Enterprises/Corporate Social Responsibility